(untitled) (Contemporary Mathematics, 2024)
The paper deals with the solvability of the following doubly singular boundary value problem naturally arising in the study of the existence and properties of travelling waves for reaction-diffusion-convection equations governed by the p-Laplacian operator. Here c, α are real parameters, with α > 0, and f, g, h are continuous functions in [0, 1], with h(0) = h(1), h(u) > 0 in (0, 1).